Soul machine : the invention of the modern mind - Makari, George (W. W. Norton & Company, Inc., 2015)
A comprehensive history of the creation of the modern Western mind recounts how crises in religious authority and the scientific revolution led to medical, literary and philosophical questions about the nature of human inner life. --Publisher